Design of home fire detection system based on wireless multi-sensor data fusion - Wenbin CHENG; Lei DU; Yiyi LIU (Dianxin kexue)
Aiming at the shortcomings of false alarm and leakage alarm in the existing fire detection system and the complicated wiring,high cost and poor flexibility of the traditional wired fire detection system,a set of home fire detection system based on wireless multi-sensor data fusion was designed,to detect the fire safety hazards caused by kitchen equipment aging,electrical wiring aging or electrical equipment aging.The design of multi-sensor data fusion algorithm,fire detection system hardware framework and software implementation were described in detail.The simulation results show that the scheme has the characteristics of high accuracy and flexibility.